A record of the coyote (Carnivora: Canidae) in the Calakmul Biosphere Reserve, Mexico (UNED Research Journal, 2020)
In recent years the coyote (Canis latrans) has expanded its range in the tropical areas of Mexico and Central America. We report the first record of a coyote in the Calakmul Biosphere Reserve in the southeastern, Mexico. Using photo trapping, from December 2018 to June 2019, tree photographs of coyotes were obtained from a site located in the center of the southern core area of the reserve.
Keywords: canids; Campeche; phototrapping; new records; mammals